TECHNIQUE AND QUALITY OF ENGLISH – INDONESIAN TRANSLATION OF PUN IN TOLKIEN’S THE HOBBIT - Yolanda, Rizky; Yuliasri, Issy (English Education Journal, 2016)
Puns occupy a significant position in literature. The people are getting more and more excited when the novel uses puns. Pun, however, might be challenging for translators to translate pun which is closely related to the source language culture. Therefore this study is carried out in order to find out the kindsoftranslation techniques used, and to assess the quality of English – Indonesian translation English – Indonesian Tolkien’s The Hobbit.The object of this study is English - Indonesian pun translation of J.R.RTolkien’s The Hobbit.The result of the analysis shows that there are 243 puns found in J.R.R Tolkien The Hobbit.There are three kinds of pun are found in this novel. Paronymy dominates in 231 data, Homonymy with 11 data, Homophony with 1 datum. The analysis on translation techniques shows that there are six techniques used. Pun to Non Pun technique, Punoid, Pun to Pun, Non Pun to Pun, then Pun in ST is copied to Pun in TT and Pun to Zero. The analysis on the translation quality shows that 56 translations are considered as accurate, and 187 translations are considered as less accurate. In acceptability level, 116 translations belong to acceptable, and 127 translations belong to less acceptable. Readability level shows that 133 translations are categorized as high readability, and 110 translations are categorized as sufficient readability.